[Concerning L. Luzzatti, La embriologia e la evoluzione delle costituzioni politiche, 1880] - Luca Ciancio (Scienza & Politica, 2013)
Luca Ciancio discusses Luigi Luzzatti’s article starting from a reflection about the ubiquity of the biological metaphors used by him in order to reason on the method of constitutional science. Luzzatti bases on the classic distinction between historic "organic" constitutions, i.e. the British one, which is a true and spontaneous incarnation of the "national character", and abstract "mechanic" constitutions, artificially imposed by reason and therefore instable. In the late positivistic era the same recourse to a metaphorical evolutionistic repertoire, like the one of the embryologic dynamic of the constitutions, on the one defines hand Luzzatti’s intent as a subscription to historicism and organicism, which is typical of his epoch, and on the other hand the free recourse to biology allows him to discuss cognitive strategies that are useful to constitutional science and freed from a dogmatic notion of scientificity. Through Luzzatti's text, though, Ciancio underlines the meaning and the function of an evolutionistic paradigm which defined in a rigid and ideological way the historic investigation and which Luzzatti uses to recall an idea of order, restoration and continuity